NGF Signaling Exacerbates KOA Peripheral Hyperalgesia via the Increased TRPV1-Labeled Synovial Sensory Innervation in KOA Rats - Zixiu Liu; Mingchao Li; Li Zhang; Xiaoqing Shi; Taiyang Liao; Lishi Jie; Likai Yu; Peimin Wang (Pain Research and Management)
Objectives. Knee osteoarthritis (KOA) pain is caused by nociceptors, which are actually sensory nerve fiber endings that can detect stimuli to produce and transmit pain signals, and high levels of NGF in synovial tissue led to peripheral hyperalgesia in KOA. The purpose of this study is to investigate how sensory nerve fibers respond to the NGF/TrKA signal pathway and mediate the peripheral hyperalgesia in KOA rats. Methods. Forty SD male rats were randomly divided into 4 groups: normal, KOA, KOA + NGF, and KOA + siRNA TrKA. KOA model rats were induced by anterior cruciate ligament transection (ACLT). Mechanical and cold withdrawal thresholds (MWT and CWT) were measured 4 times in each group. The synovial tissues were harvested on day 28, and the expressions of NGF, TrKA, TRPV1, IL-1β, and PGP9.5 were determined using western blot, qPCR, and immunofluorescence staining. The primary rat fibroblast-like synoviocytes (FLSs) and DRG cells were divided into 4 groups as in vivo. The expressions of NGF, TrKA, TRPV1, and CGRP in vitro were determined using western blot and qPCR. Results. KOA and intra-articular injection with NGF protein increased both mRNA and protein levels, not only TRPV1, PGP 9.5, and IL-1β in the synovial tissue, but also TRPV1, PGP 9.5, and S100 in the DRG tissue, while above changes were partly reversed after siRNA TrKA intervention. Besides, siRNA TrKA could improve peripheral hyperalgesia and decreased the TRPV1 positive nerve fiber innervation in synovial tissue. The results in vitro were consistent with those in vivo. Conclusion. This study showed the activation of the NGF/TrKA signaling pathway in KOA promoted the release of pain mediators, increased the innervation of sensory nerve fibers in the synovium, and worsened peripheral hyperalgesia. It also showed increased TRPV1 positive sensory innervation in KOA was mediated by NGF/TrKA signaling and exacerbated peripheral hyperalgesia.